Coagulopathy in SARS-CoV-2 Infected Patients: Implication for the Management of COVID-19 - Getu, Sisay (J Blood Med, 2021)
COVID-19 disease has led to an extraordinary inclusive health crisis globally. Elevation of D-dimer is the major remarkable abnormal coagulation test in seriously ill COVID-19 patients. In nearly 50% of COVID-19 patients, the value of D-dimer was significantly enhancing. Recent literature indicated that COVID-19 patients were at higher risk of developing disseminated intravascular coagulation. Pro-inflammatory cytokines and chemokines are some of the factors leading to these conditions. The majority of COVID-19 patients showed a higher profile of pro-inflammatory cytokines and chemokines in severe clinical conditions. Tumor necrosis factor-α (TNF-α) and interleukins (ILs) elevated in COVID-19 infected patients. TNF-α, IL-6, and IL-1 are major cytokines vital for the inhibition of intrinsic anticoagulant pathways. COVID-19 becomes a higher complication with a significant effect on blood cell production and hemostasis cascades. Deep vein thrombosis and arterial thrombosis are common complications. Changes in hematological parameters are also frequently observed in COVID-19 patients. Especially, thrombocytopenia is an indicator for poor prognosis of the disease and is highly expected and aggravates the likelihood of death of SARS-CoV-2 infected individuals. Thrombopoiesis reduction in COVID-19 patients might be due to viral abuse of the bone marrow/the viral load may affect thrombopoietin production and function. In other ways, immune-inflammation-mediated destruction and increased consumption of platelets are also the possible proposed mechanisms for thrombocytopenia. Therefore, the counting of platelet cells is an easily accessible biomarker for disease monitoring. All SARS-CoV-2 infected patients should be admitted and identifying potential higher-risk patients. It is also obligatory to provide appropriate treatments with intensive care and strict follow-up. In addition, considerations of chronic diseases are essential for better prognosis and recovery. The current review discusses coagulopathy among SARS-CoV-2 infected individuals and its complication for the management of the disease.